Kewenangan Komisi Pemberantasan Korupsi (KPK) dalam Penangulangan Tindak Pidana Korupsi - Yani Andriyani; Suwari Akhmaddhian; Diky Hikmatul Fittra (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
KPK is a new institution with the authority which is often referred to as a superbody institution which has extra authority compared to other state institutions. The Corruption Eradication Commission was formed with the aim of increasing the efficiency and effectiveness of efforts to eradicate corruption. Corruption is indeed an extraordinary crime, and therefore its eradication must also be carried out in an extraordinary way. The purpose of this paper is to find out how the authority of the Corruption Eradication Commission (KPK) in the Corruption Eradication Code of Ethics and how the Theory of the State of Law in the Eradication of Corruption Crimes. The method used in writing this paper is normative juridical. Sources of data used are primary and secondary data sources. The results of this study are in carrying out the task of coordinating with agencies, supervising agencies, conducting investigations, investigations, and prosecutions, taking preventive actions, monitoring the implementation of state government, the authority of the Corruption Eradication Commission is regulated in Articles 7 to 14 of the Law. Law Number 30 of 2002 concerning the Commission for the Eradication of Criminal Acts of Corruption. In order to achieve the legal objectives as stated in Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia that Indonesia is a state of law, a State Institution that is Special in terms of eradicating Corruption Crimes is needed for the implementation of law and justice.